2019
DOI: 10.1007/s11864-019-0607-8
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Therapy and Immunotherapy for Melanoma in Japan

Abstract: Opinion statementMelanoma has several clinically and pathologically distinguishable subtypes, which also differ genetically. Mutation patterns vary among different melanoma subtypes, and efficacy of immune-checkpoint inhibitors differs depending on the subtype of melanoma. In spite of the recent revolution of systemic therapies for advanced melanoma, access to innovative agents is still restricted in many countries. This review article aimed to describe the epidemiology and current status of systemic therapies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
90
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 97 publications
(92 citation statements)
references
References 84 publications
(73 reference statements)
2
90
0
Order By: Relevance
“…Several studies have shown that the curative effect of the PD-1 antibody combined with chemotherapy, targeted drugs, and multiple immune checkpoint drugs was better than that of the administration of a single drug. The effect of getting twice the result with half the effort was obtained [37][38][39][40][41][42] . It should be noted that the therapy with PD-1 or PD-L1 antibody is known to be effective mainly through the immunological mechanism playing the antitumor role;…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that the curative effect of the PD-1 antibody combined with chemotherapy, targeted drugs, and multiple immune checkpoint drugs was better than that of the administration of a single drug. The effect of getting twice the result with half the effort was obtained [37][38][39][40][41][42] . It should be noted that the therapy with PD-1 or PD-L1 antibody is known to be effective mainly through the immunological mechanism playing the antitumor role;…”
Section: Discussionmentioning
confidence: 99%
“…Five of 25 patients (20%) had a partial response (objective response rate of 20%) and 13 (52%) patients had stable disease. Additionally, there was a maintained clinical benefit, with a median duration of response 12.0 months (95% CI: 3.7 not reached) [32,33]. The NivoMes Mesothelioma, a Review of Current Guidelines DOI: http://dx.doi.org/10.5772/intechopen.93569 study, which evaluated nivolumab in unselected patients with previously treated mesothelioma reported response rates of 28%.…”
Section: Immunotherapy and Targeted Therapiesmentioning
confidence: 99%
“…Subgroup analysis in the PD-L1-positive population (cutoff > 5%) showed a response rate of 14% [34]. Novel vaccine approaches using MPM neoantigens identified by gene sequencing are also entering clinical trial on the basis of early animal studies [33].…”
Section: Immunotherapy and Targeted Therapiesmentioning
confidence: 99%
“…Nearly two-thirds of AM was diagnosed at stage II or above, while only approximately one-third of cutaneous melanoma was diagnosed at stage II or above. Therefore, most patients have developed distant metastasis when diagnosed with AM, and systemic treatment for advanced AM is of great significance ( 3 ).…”
Section: Introductionmentioning
confidence: 99%